(untitled) (Ius Novum, 2024)
The study is an original scientific article devoted to the issues of proposed changes in the EU regulations on counteracting money laundering (the so-called ‘AML package’). A significant part of the amended provisions of EU legal acts will be governed by EU Regulations and, as such, they will be directly applicable. This situation justifies the need for an in-depth analysis. On the other hand, those provisions which remain in the form of directives raise certain reservations. Therefore, the aim of this article is to analyse the nature and scope of the comprehensive amendment to the AML regulations using a formal-dogmatic method. Based on this analysis, conclusions were drawn regarding the assessment of the legitimacy and possible effectiveness of the proposed regulations in combating money laundering. The conclusion also highlights the inaccuracies and deficiencies they are burdened with, allowing for de lege ferenda postulates concerning the desired correction of the regulations.